Analysis of Fuel Criticality during Severe Accidents - Bilodid, I.; Duspiva, J. (Ядерна та радіаційна безпека, 2015)
Interest in the analysis of beyond design basis accidents, involving a combination of several failures with fuel damage, has increased throughout the world after the Fukushima accident. Stress tests were performed at NPPs, and development of severe accident management guidelines was started. These activities necessitated calculations to analyze the probability of beyond design basis accidents and assess their initiating events and consequences. One of the aspects in analysis of beyond design basis accidents is to determine the potential for re-criticality during such accidents. The paper provides results of some criticality safety calculations for VVER reactors performed, in particular, by ÚJV Řež and SSTC NRS experts. It is shown how criticality can occur in different severe accident phases. Во всем мире после аварии на АЭС Фукусимы вырос интерес к анализу запроектных аварий: с наложением нескольких отказов, с повреждением топлива. На АЭС были проведены стресс-тесты, начали разрабатываться руководства по управлению тяжелыми авариями. Как следствие такой деятельности, выросла необходимость в проведении расчетных анализов как вероятности возникновения запроектных аварий, так и исследование условий возникновения аварий и их последствий. Одним из аспектов анализа запроектной аварии является определение возможности возникновения критичности в течение аварии. В статье приведены результаты некоторых расчетных анализов безопасности критичности, которые были сделаны или применимы для реакторов ВВЭР. У всьому світі після аварії на АЕС Фукусіми збільшився інтерес до аналізу запроектних аварій з накладанням кількох відмов та з пошкодженням палива. На АЕС проведено стрес-тести, почали розроблятися керівництва з управління важкими аваріями. Внаслідок такої діяльності зросла потреба в проведенні розрахункових аналізів як імовірності виникнення запроектних аварій, так і дослідження умов виникнення аварій та їх наслідків. Одним з аспектів аналізу запроектної аварії є визначення можливості виникнення критичності протягом аварії. У статті наведено результати деяких розрахункових аналізів безпеки критичності для реакторів ВВЕР, зроблених, зокрема спеціалістами ÚJV Řež та ДНТЦ ЯРБ. Показано можливість виникнення критичності на різних стадіях протікання важкої аварії.